The Agreement Between of Vitek 2 and HybriSpot 24 in Identification of SHV-Type ESBLs and CTX-M-Type ESBLs from ESBL Producing Enterobacteriaceae Isolat - Jihan Samira, Mujahidah , Helmia Farida (International Journal of Advanced Science and Technology, 2020)
The identification of extended-spectrum beta-lactamase (ESBL) types is important for selecting antibiotics in treating patients infected by ESBL-producing Enterobacteriaceae. This can be done phenotypically and genotypically. Vitek 2 phenotypically identifies ESBL types such as CTX-M and SHV. HybriSpot 24 genotypically identifies CTX-M and SHV-encoding genes (blaCTX-M and blaSHV respectively). The objective of this study was to identify or characterize types of ESBL enzymes and to measure the agreement between Vitek 2 and HybriSpot 24 in detecting SHV and CTX-M ESBL types. The methodology of this research is by taking 30 isolates samples from Dr. Kariadi Hospital’s inpatients, which had been phenotypically identified as ESBL-producing Enterobacteriaceae by Vitek 2 in Dr. Kariadi Hospital. The genotypic test was performed using HybriSpot 24 in Indonesia University Hospital, Jakarta. The agreement between these two methods was analyzed using Cohen’s Kappa coefficient. The result from this study was obtained from 30 isolates, one was excluded because of contamination, 20 were Escherichia coli and 9 were Klebsiella pneumoniae. Vitek 2 identified enzyme-types in 5 (17%) isolates, namely 3 (10%) CTX-M and 2 (7%) SHV. HybriSpot 24 identified ESBL-encoding genes in 27 (93%) isolates, that is 15 (52%) blaCTX-M, 8 (27%) both blaCTX-M and blaSHV, 2 (7%) blaSHV, and 2 (7%) both blaSHV and blaGES (a carbapenemase-encoding gene). The latter two isolates’ MIC for meropenem/ertapenem was ≤0.025. The conclusion of this study is that CTX-M is the most prevalent ESBL-type in Dr. Kariadi Hospital and the agreement between Vitek 2 and HybriSpot 24 in identifying CTX-M type was very poor (κ=3,6%) and poor in SHV type (κ=24,7%).